(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The purpose of this research is to focus on whether there has been a significant change in the demand for both of these mediums, physical and online shopping, for the initial year and the succeeding years of the pandemic. Aside from that, the study also looks into the consumer medium preferences, as well as the product preferences that consumers typically purchase on such media. The study reveals that the majority of respondents chose online shopping as their preferred method during the pandemic as it was convenient and accessible during that time; however, as shopping policies got lightened by the year 2022, respondents started to use physical shopping methods again as it became more accessible that time due to government lifting some shopping restrictions. This study recommended that online shops should optimize their shop by making sure their website is user-friendly and easy to navigate, provide detailed product descriptions and images to help customers make informed purchasing decisions, and offer free delivery or curbside pickup options to encourage customers to shop online, and physical shops should Implement measures to reduce the spread of the virus, such as enforcing social distancing, requiring masks, providing hand sanitizer, and disinfecting high-touch surfaces regularly. It’s important to know the demand for online and physical shopping; it can help businesses make strategies to improve their business; customers consider three things when choosing their mode; first is if it is convenient, we have to think if doing it or choosing will be convenient to us or if it can save us time and effort. The second is accessibility. The researchers have to consider if it’s accessible in our area or at the current time since we are still in a pandemic. There are shops that are still closed because of the pandemic. Lastly is affordability. When the pandemic started, our country’s economy dropped. A lot of people lost their jobs, and businesses were closed, which stopped a lot of people from earning. That’s why considering if it is affordable is also important. Researchers may help future researchers by giving them information about the fluctuations in demand for click-and-mortar shopping in the new normal.